A General Overview on Labuan, Malaysia's International Offshore Financial Center - Foong, Kai Ee (1998)
Labuan, Malaysia's International Offshore Financial Center was established in 1990 and many efforts has been placed by the government to develop Labuan into one of the Asia's premier international offshore center. However, not many people are aware of the existence of this offshore center including Malaysians. This paper is set with an objectives to introduce Labuan to Malaysians and the world. Firstly, an introduction on the location and history- of Labuan is discussed. This follows by a brief introduction of regulatory bodies governing Labuan. Further discussion will be on the type of services provided and procedure to get on to those business. This paper then continue to elaborate tax regime and legislation in Labuan respectively. Then a comparison between Singapore, Hong Kong and Labuan as Asia's premier offshore financial center is made. Lastly a discussion is then made on government's role in promoting Labuan IOFC The information and materials for this paper were mainly collected from articles from business magazine and Labuan website. Although Labuan is relatively small compared to other offshore financial centers in term of number of companies and value of funds managed, it has the potential to become one of the popular offshore center in Asian one day in the future.